Preparation of Activated Carbon Based on Oil Palm Waste for Ammonia Removal - Ivan Daniel; Rini Selly; Jasmidi Jasmidi (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
The aim of this study Industri is to reduce ammonia concentration in tannery waswater using Oil Palm waste. Palm oil is one of the strategic industry that is engaged in agriculture (agro-based industry) that many develop in tropical countries such as Indonesia. Palm oil plantations produce solid waste, one of which is an empty bunch. and the palm oil processing industry produces the liquid waste of one of them ammonia. By looking at the opportunity how to cope with the waste of ammonia derived from the processing of palm oil by making biosorbents from solid waste of empty palm plants that utilization of empty waste plants is still not maximal. With some treatment and tested with BET to see the surface area and total volume of pores after and before the treatment of activated carbon.